Impulsivity, Social Support and Depression Are Associated With Latent Profiles of Internet Addiction Among Male College Freshmen - Zhang, Yue; Liu, Zhuang; Zhao, Yuhong (Frontiers in Psychiatry, 2021)
Background: The rate of internet addiction is increasing in college students. During the COVID-19 epidemic, home isolation increased the likelihood of students becoming addicted to the Internet. The first year at college is a particularly vulnerable period for internet addiction. Our study aimed to assess the relationship between impulsivity, social support, depression and internet addiction among college male freshmen. Materials and Methods: The current study utilized latent profile analysis (LPA) to identify at-risk profiles among 734 college freshmen (100% male) based on their Internet Addiction Test item ratings. We compared the levels of impulsivity, social support and depression among different profiles and investigated whether these variables could predict each latent internet addiction class. Results: LPA resulted in three distinct profiles: the low internet addiction group (42.10%), the moderate internet addiction group (35.70%) and the high internet addiction group (22.20%). Impulsivity and depression increased with internet addiction severity levels, whereas social support was inversely related to the severity of internet addiction. Male freshmen with high impulsivity, low social support and high depression were more likely to be included in the high internet addiction group. Conclusion: This study highlights that impulsivity, social support and depression may predict internet addiction in college students. Our findings have important practical implications for college educators and counselors in developing interventions for internet addiction, especially during the COVID-19 epidemic.